Identification of the powdery mildew caused by Erysiphe trifoliorum (Wallr.) U. Braun on Melilotus officinalis. (Boletín Micológico, 2016)
High incidence of the powdery mildew Erysiphe trifoliorum was diagnosed on Melilotus officinalis in Buenos Aires. Conidial germination assays were conducted in order to identify the pathogen to the species level. Images of the conidia, germination pattern, and conidiogenous cells are provided.